GMP compliance in Malaysia: meeting global standards for quality and safety in pharmaceutical, health supplement, traditional and cosmetic industries / Assoc. Prof. Dr. Meor Mohd Redzuan Meor Mohd Affandi - Meor Mohd Affandi, Meor Mohd Redzuan (Faculty of Pharmacy, 2023)
In the field of pharmaceutical production, Good Manufacturing Practices (GMP) play a critical role in ensuring the safety and quality of products. Defined by the World Health Organization (WHO, 2021), GMP is a component of quality assurance that guarantees products are consistently produced and controlled to the appropriate quality standards. The principle behind GMP is that quality is integrated into the production process rather than simply tested in the final product. This ensures that the product not only meets final specifications but is also manufactured using the same procedures and under the same conditions every time.